2008
DOI: 10.1186/1465-9921-9-31
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal association of body mass index with lung function: The CARDIA Study

Abstract: Background: Lung function at the end of life depends on its peak and subsequent decline. Because obesity is epidemic in young adulthood, we quantified age-related changes in lung function relative to body mass index (BMI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
109
2
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(141 citation statements)
references
References 34 publications
19
109
2
11
Order By: Relevance
“…We found ,12% of our lung cancer cases had restrictive lung function comparable to other studies [21]. However, we did not find any difference in restrictive lung function between cases and controls, although differences in BMI may be, in part, obscuring any difference [18,20].…”
Section: Thoracic Oncology Rp Young Et Alsupporting
confidence: 64%
See 1 more Smart Citation
“…We found ,12% of our lung cancer cases had restrictive lung function comparable to other studies [21]. However, we did not find any difference in restrictive lung function between cases and controls, although differences in BMI may be, in part, obscuring any difference [18,20].…”
Section: Thoracic Oncology Rp Young Et Alsupporting
confidence: 64%
“…GOLD 1+) is commonly seen [18], and 2) best reflect older definitions of COPD (European Respiratory Society and ATS) [5]. The prevalence of restrictive lung function (FEV1/FVC .70% and FVC ,80%) was comparable in the cases and controls (,12%) but may in part reflect differences in body mass index (BMI) between the cases and controls [18,20]. No relationship with lung function (or COPD prevalence) was seen after subgrouping lung cancer cases according to staging although COPD prevalence was slightly higher in small cell and squamous cell lung cancers (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The association between lung dysfunction and overweight has been demonstrated by the reduction of FVC and other lung volumes. The compliance decrease of the thoracic wall or its inactivity, besides the expiratory reserve volume reduction, related to the abdominal fat accumulation and above the rib cage plus the increase on the endurance of the respiratory tract are aspects that can explain the fact [17][18][19] . The FVC and MPT presented similar values on the three nutritional statuses.…”
Section: Discussionmentioning
confidence: 99%
“…The CARDIA study [21] investigated the dependence of lung function on BMI, and found substantial lung function loss in people who were overweight as youngsters. They concluded that "the obesity epidemic threatens the lung heath of the general population".…”
Section: Comparing the Performance Of The Models In A Realistic Scenamentioning
confidence: 99%
“…To study the impact of a small sample on each parameterisation under the data generated according to (21) and (22), and (23) and (24), we analysed 100 datasets each containing 200 observations, and a further 100 datasets containing 2,000 observations. Average F and adjusted R 2 values are given in Table 10, implying that the instrument is considered 'weak' when a 1 = 0.3.…”
Section: A Further Examplementioning
confidence: 99%